Cryptography Using Chaos In Communication Systems. Issue 1 (March 2021) - Raja Kumar, R.; Pandian, R.; Prem Jacob, T.; Pravin, A.; Indumathi, P.
Abstract: A new and unexplored area in the field of cryptography is the use of chaotic systems to encrypt data. The purpose of this paper is to present how the principles of chaos theory can be applied in the field of cryptography. A cipher that uses chaos dynamics is presented that has very good statistical properties.